Human Trafficking In The Islamic View (Comparative Study Of Al-Azhar And Al Misbah Interpretation) - Harahap, Sayla Ar Rahmah Hafiidzah; Indra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to examine and compare Islamic views on human trafficking based on two prominent tafsir works, namely Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Misbah by M. Quraish Shihab. Human trafficking, as a form of modern slavery, is a global problem that is very contrary to human values. From an Islamic perspective, protection of human dignity and rights is strongly emphasized, including the prohibition of all forms of human exploitation. Tafsir Al-Azhar, with a contextual and sociological approach, emphasizes the importance of maintaining human honor and freedom and condemns slavery in the socio-cultural context of Indonesia. On the other hand, Tafsir Al-Misbah, with a linguistic and historical approach, highlights human trafficking as a violation of the principles of justice and humanity in Islamic teachings. This study found that although the two tafsirs have different approaches, both are in line in the view that human trafficking is an act that is prohibited in Islam and contrary to the universal values taught by the Qur'an.